Effects of chemotherapeutics against experimentally injured stinging catfish Heteropneustes fossilis - Neowajh, Md Sharif; Rashid, M Mamnur; Asif, Abdulla Al; Zafar, Md Abu; Hossain, Amir (Asian Journal of Medical and Biological Research, 2018)
Effects of different chemotherapeutics were examined against experimentally infected stinging catfish Heteropneustes fossilis. Fish were collected from a fish market in Mymensingh, acclimatized for 7 days in laboratory condition from January to February, 2016 in aquaria at Fish Clinic of Bangladesh Agricultural University, Mymensingh, experimentally injured by using forceps and knife and waited seven days for the establishment of infection. Before starting chemotherapeutic trial, it was confirmed that the fish were infected with microorganisms by clinical diagnosis in laboratory condition. They showed hemorrhages and ulcerative lesions over the infected area. A total of 80 such experimentally infected stinging catfish having average body weight of 18 g were used for the experiment. Two chemotherapeutics: antibiotic, Eryvet (erythromycin thiocyanate INN, sulphadiazine (NaUSP) & trimithoprim BP) and antifungal, methylene blue were used in separate and combined treatment with three different doses of antibiotic. The same dose of methylene blue, 0.2 mg/l, was used for separate and combined treatment by antibiotic. Doses of antibiotic (Eryvet) were 0.8 g/10 kg body weight of fish, 1g/10 kg body weight of fish and 1.2 g/10 kg body weight of fish as lower dose, recommended dose and higher dose respectively. For combined treatment the above different doses of antibiotic and the same dose of antifungal were used. Water was exchanged regularly. The chemotherapeutic trial was conducted for 7 days and observation was continued for another 8 days to observe the effect of treatment. Combined treatment with the recommended dose of the antibiotic and methylene blue showed the best result where 90% fish were recovered. By the treatment with the higher dose of the antibiotic 70% fish were recovered. Antifungal treatment showed that 20% fish were recovered. All the fish in negative control aquarium died. Asian J. Med. Biol. Res. December 2017, 3(4): 476-487